What is the best first-line combination regimen for advanced EGFR-mutated non-small cell lung cancer: a network meta-analysis and systemic review - Yang, Chuang; Wang, Yunfei; Sun, Yiyong; Sun, Ying; Zhang, Rongyu; Wang, Chengjun; Song, Yanan; Zhao, Wen; Li, Jisheng (Frontiers in Pharmacology, 2025)
BackgroundDespite significant survival improvements from third-generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in patients with advanced EGFR-mutated non-small cell lung cancer (NSCLC), almost all patients eventually develop resistance. Currently, some studies have confirmed that combination therapy regimens based on third-generation EGFR-TKIs can further enhance efficacy. However, it remains unknown which specific combination regimen is more effective.MethodsRandomized clinical trials comparing combination treatments involving third-generation EGFR-TKIs vs. EGFR-TKI single agent for advanced EGFR-mutated NSCLC patients were included. The primary outcome was progression-free survival (PFS), while secondary outcomes included overall survival (OS), objective response rate (ORR) and treatment-related adverse events (TRAEs). Subgroup analyses were also conducted.ResultsThe study encompassed 5 trials, involving 1791 patients. The combination of osimertinib with chemotherapy and with ramucirumab, as well as the combination of lazertinib with amivantamab, have been shown to significantly improve PFS compared to osimertinib monotherapy. The combination of osimertinib with chemotherapy and the combination of lazertinib with amivantamab resulted in a significantly higher incidence of TRAEs compared to osimertinib monotherapy and other combination regimens. Osimertinib with chemotherapy showed better PFS in almost all the subgroup analyses. In patients with brain metastases, osimertinib plus chemotherapy appeared to offer clinical benefits over other treatment strategies, although statistical significance was only observed in comparison with osimertinib monotherapy.ConclusionThis network meta-analysis suggests osimertinib plus pemetrexed-based chemotherapy as the only regimen demonstrating PFS benefits in the whole cohort and almost all the subgroup analyses, making it the optimal treatment for patients with advanced EGFR-mutated NSCLC. Given the higher incidence of grade ≥3 TRAEs, careful consideration is needed in clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier, CRD42024579401.